Language Competency, Preparedness and Attitude toward Literature Subject: A Case of Secondary Schools in Arusha City, Tanzania - Ngussa, Baraka Manjale; Faustino, Anagrolia (Advances in Social Sciences Research Journal, 2019)
While literature is an important subject in secondary school curriculum, it is optional in Tanzanian secondary schools. This leads to limited number of students who choose it even though the subject has numerous advantages. Using a sample of 197 form two students, the study sought to describe and establish relationships between students language competency, preparedness and attitude toward literature through descriptive and inferential statistics. The study concluded that students had positive attitude toward literature subject and believed that literature is one of their favorite subjects. They considered their teachers to have played their role effectively in preparing them to opt for the subject. Students further perceived that they perform very well in English subject. Furthermore, it was established that when teachers prepare students for literature subject, students’ interest in and attitude toward literature will increase. Based on conclusions above, it is recommended that teachers should use students’ positive attitude toward literature as a loop hole to guide them to opt for literature subject. There is need for teachers to continue encouraging students to take literature subject as it has been proven that the subject increases proficiency in English. Lastly, in order to increase the number of students who will take literature subject in the future, it is necessary for teachers to increase the level of preparedness for literature subject by encouraging form two students to read various literary works.